Conflict Management in Congregations - Lott, David B. (Rowman & Littlefield Publishers, 2001)
Since its inception, the Alban Institute has earned a reputation as a leader in addressing congregational conflict management issues through its research, consulting services, educational events, and particularly its publications. Drawing on this rich heritage, the first title in our new "Harvesting the Learnings" anthology series gathers 20 classic Alban works on congregational conflict into a single, indispensable volume. Conflict Management in Congregations harvests the collected wisdom of many of the key thinkers on this topic, including such past and present Alban consultants as Speed Leas, George Parsons, Margaret Bruehl, Gil Rendle, Alice Mann, and Roy Pneumann. Much of the material found here has long been unavailable but is still much in demand. Divided into three sections that explore the dynamics of conflict, conflict management techniques, and dealing with conflict in specific contexts, this book serves as a comprehensive primer that no pastor or congregational leader will want to be without.